Changes of Serum Electrolytes and Serum Vitamin C Levels in a Sample of Iraqi patients Infected with Helicobacter pylori (H. pylori) - Aburahma, Nuha Nihad A.; Kadhim, Nada A. (Iraqi Journal of Science, 2023)
Helicobacter pylori (H. pylori) is widespread and involved in the pathogenesis of the majority of stomach and duodenal diseases. Reduced stomach acidity facilitates the initial infection. Electrolytes (sodium, potassium, and chloride) are essential for the production of stomach acid. This study aimed to observe any changes in the levels of serum electrolytes (Na, K, and Cl) and serum vitamin C levels in a sample of Iraqi patients infected with H. Pylori. We studied 30 infected patients with H. Pylori and 30 matched healthy controls. The results revealed that the serum sodium, potassium, and chloride levels were significantly decreased (p = 0.002, 0.003 and 0.0001, respectively) in the patients infected with the H. Pylori group in comparison with those of the healthy controls. Also, vitamin C levels were significantly lower in patients infected with H. Pylori than in the control group (p = 0.001). The present results suggest that these changes may be attributed to or contribute to the infection itself through changes in gastric acidity, and this needs further study.